EFEKTIVITAS EKSTRAK ETANOL DAN EKSTRAK KLOROFORM SIPUT ONCHIDID (Onchidium thyphae) SEBAGAI PENUMBUH RAMBUT PADA TIKUS (Rattus norvegicus) - Wijianto, Bambang; Wijianto, Bambang Wijianto; Pratiwi, liza; Utami, Amanda Yanasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Hair loss is a problem that can affect appearance. A natural ingredient that can address hair loss treatment is the extract of the onchidiid snail. This study aims to test the hair growth effectiveness of ethanol and chloroform extracts of the onchidiid snail on white rats (Rattus norvegicus). The test groups of rats were divided into several groups: the Negative Group (CN), the Positive Group (CP) with candlenut oil, Treatment Group I (K1) with Chloroform Extract of the Onchidiid Snail, and Treatment Group II (K2) with Ethanol Extract of the Onchidiid Snail. Hair growth length was measured daily and processed using Image J software. The hair growth effectiveness test showed that over 14 days, the chloroform extract (K1) produced faster results compared to the other three groups, with a hair growth result of 1.61 cm on the 14th day. The findings of this study conclude that the chloroform extract of the onchidiid snail effectively promotes hair growth in male Wistar strain white rats.